Climate Change Education through Narrative Inquiry - Sherpa, Pasang Dolma (Journal of Transformative Praxis, 2021)
This article addresses Climate Change Education (CCE) and its interface with Indigenous knowledge. Specifically, I explore the potential for transformation towards more holistic climate change education that balances science and Indigenous knowledge. However, the study details the persistent focus of contemporary education on climate science without interfacing with Indigenous knowledge, cultural values, and associated practices that contribute to climate change resilience. This article tackles this gap and the requisite transformation in climate change education through narrative inquiry.